2013
DOI: 10.1016/j.jmbbm.2013.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Indentation damage and crack repair in human enamel

Abstract: Tooth enamel is the hardest and most highly mineralized tissue in the human body. While there have been a number of studies aimed at understanding the hardness and crack growth resistance behavior of this tissue, no study has evaluated if cracks in this tissue undergo repair. In this investigation the crack repair characteristics of young human enamel were evaluated as a function of patient gender and as a function of the distance from the Dentin Enamel Junction (DEJ). Cracks were introduced via microindentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 31 publications
0
21
1
Order By: Relevance
“…New treatments aimed at replacing the enamel proteins post-whitening may be necessary. A recent preliminary study reported that enamel undergoes a process of crack-healing involving crack closure [82]. The question that arises is whether this healing process is purely cosmetic, or if it also restores the integrity of the tissue as well.…”
Section: Discussionmentioning
confidence: 99%
“…New treatments aimed at replacing the enamel proteins post-whitening may be necessary. A recent preliminary study reported that enamel undergoes a process of crack-healing involving crack closure [82]. The question that arises is whether this healing process is purely cosmetic, or if it also restores the integrity of the tissue as well.…”
Section: Discussionmentioning
confidence: 99%
“…As previously mentioned, the proteins play a critical role in the toughing mechanisms that contribute to the crack growth resistance of these materials. But the proteins also appear to act in repairing damage within mineralized tissues [12,165]. That topic has not been pursued in detail and has remained controversial.…”
Section: Challenges and Future Workmentioning
confidence: 99%
“…Boyde observed the deposition of new mineral within the crack and speculated that some cracks could “anneal” and “heal” in situ without the removal of the bulk damaged matrix. Biomineralization studies have clearly shown that the physicochemical dissolution and deposition of bone minerals constantly occur on the bone‐fluid interfaces as found in the mineralizing osteoid and in the process of refilling cracks in enamel . Besides minerals, other non‐collagen proteins may also be involved in the repair process.…”
Section: Discussionmentioning
confidence: 99%